KONFLIK UMAT HINDU - MUSLIM DI INDIA ERA PEMERINTAHAN NARENDRA MODI - Yunariono, Bastian - (Jurnal Paradigma, 2023)
AbstractThe Hindu-Muslim conflict in India has been a systemic conflict in the last few decades. This communal conflict has increased since PM Narendra Modi from the Bharatiya Janata Party (BJP) hold power in 2014. To explain this problem this research uses the perspective of communalism Surya Prakash Upadhay and Rowena Robinson who state that Indian society is constructed based on lines of homogeneous religious identity. Economic, social and political interests are under religious identity. Communalism is used by the elite and politicians as an instrument to achieve their goal. The method used is a qualitative method with secondary data. The results of this study prove that the conflict between Hindu-Muslims in India is systemic because it is driven by Hindu nationalist interest groups such as the RSS which wants the construction of India based on Hindutva ideology. This conflict has become more massive as a result of religion being used by BJP politicians as an instrument or means to win sympathy for Hindus in India.Keywods: conflict, Hindu Muslim, communalism, Bharatiya Janata Party, Rashtriya Swayamvevak Sangh